Teachers' Perspectives on CLIL and Classroom Innovation in a Method based on Drama Games - Stephan Breidbach; José Medina-Suárez (Universidad de Navarra, 2016)
This paper presents an analysis of a set of semi-structured interviews conducted with a group of CLIL and non-CLIL teachers from Germany and Spain on topics related to CLIL and the use of drama games. The purpose of this study is to determine the conceptualizations and attitudes they have about these two methods and the combination of both. We conducted a thematic analysis and a case study, and determined the similarities and differences among the teachers interviewed. We also examined the degree of 'investment' (Norton, 2013) they may be willing to make regarding a new method resulting from the project 'playingCLIL'.